PENERAPAN TEORI SOSIAL DALAM PEMBENTUKAN KARAKTERANAK USIA DINI - RIASTI, NOVIDA (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This research aims to explore the influence of social theory in the formation of children's character at Puspita Malang Kindergarten. The method used is descriptive with a qualitative approach and case studies. Data was collected through observation, documentation and interviews. The data analysis technique used involves triangulation of relationship models, which includes data reduction, data presentation, and drawing conclusions. The research subjects consisted of parents, educators and the community at Puspita Malang Kindergarten. The results of the analysis show that early childhood character development is influenced by three main factors: 1) family environment, 2) school environment, and 3) community environment. They learn through imitation of adults they consider as role models, such as parents, teachers or community figures. As a teacher, you must have a positive and optimistic attitude in order to help the younger generation develop their character.figures. As a teacher, you must have a positive and optimistic attitude in order to help the younger generation develop their character. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi pengaruh teori sosial dalam pembentukan karakter anak di TK Puspita Malang. Metode yang digunakan adalah deskriptif dengan pendekatan kualitatif dan studi kasus. Data dikumpulkan melalui observasi, dokumentasi, dan wawancara. Teknik analisis data yang digunakan melibatkan triangulasi model hubungan, yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Subjek penelitian terdiri dari orang tua, pendidik, dan masyarakat di TK Puspita Malang. Hasil analisis menunjukkan bahwa perkembangan karakter anak usia dini dipengaruhi oleh tiga faktor utama: 1) lingkungan keluarga, 2) lingkungan sekolah, dan 3) lingkungan masyarakat. Mereka mempelajari melalui tindakan peniruan kepada orang dewasa yang mereka anggap sebagai panutan, seperti orang tua, guru, atau tokoh Masyarakat. Sebagai seorang guru harus mempunyai sikap positif dan optimis agar dapat membantu generasi muda mengembangkan karakter mereka.